2021
DOI: 10.7150/ijbs.56733
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1-induced miR-552 expression contributes to pancreatic cancer progression by targeting multiple tumor suppressor genes

Abstract: Dysregulation of microRNAs (miRNAs) plays important roles during carcinogenesis. Forkhead box M1 (FOXM1), a well-known oncogenic transcription factor, has been implicated in the progression of multiple cancer types. To find out FOXM1-induced abnormal miRNAs in pancreatic cancer, we analyzed TCGA database and figured out miR-552 as the most relevant miRNA with FOXM1. Molecular experimental results demonstrated that FOXM1 transcriptionally activated miR-552 expression by directly binding to the promoter region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Previous reports discovered that miR-552-3p played different functions in different diseases. It was reported that miR-552-3p exerted a promoting role in pancreatic cancer [32], gastric cancer [33], and osteosarcoma [34]. Moreover, miR-552-3p could decrease LDL-C in high fat-fed mice [35] and ameliorate hepatic glycolipid metabolism disorder in high fat-high fructose diet-fed mice [36].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports discovered that miR-552-3p played different functions in different diseases. It was reported that miR-552-3p exerted a promoting role in pancreatic cancer [32], gastric cancer [33], and osteosarcoma [34]. Moreover, miR-552-3p could decrease LDL-C in high fat-fed mice [35] and ameliorate hepatic glycolipid metabolism disorder in high fat-high fructose diet-fed mice [36].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al observed that FOXM1 plays a regulatory role in tumor proliferation, invasion, chemotherapy resistance, and genomic mutation by regulating downstream ovarian cancer-related genes (44). In a study focus on pancreatic cancer, Wang et al thought that upregulated FOXM1 will activate the production of miRNA-552 and in uence the expression of DACH1, PCDH10, and SMAD4, which promotes the development of pancreatic cancer (45). Moreover, the transcriptional regulation of FOXM1 has also been reported in head and neck cancer, prostatic cancer, breast cancer, hepatocellular carcinoma, and other cancers ( 46),( 47), ( 48), (49).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there are emerging possible adjuvant strategies to prolong postoperative survival time. Targeting the YAP-autophagy circuit and the FOXM1-miR-552-DACH1/PCDH10/SMAD4 axis may offer new opportunities for therapeutic intervention against PAC ( 30 , 31 ). In addition, leflunomide plus gemcitabine has demonstrated inhibition of the growth of pancreatic ductal adenocarcinoma ( 32 ).…”
Section: Discussionmentioning
confidence: 99%